Kajian Karakteristik Nelayan Terhadap Akses Sumber Informasi ; (Kasus Di Desa Parangtritis Kecamatan Kretek Kabupaten Bantul Yogyakarta) - E. Sugiharto; A.V.S. Hubeis; Gardjito .; F. Rohadji (Institut Pertanian Bogor, 2008)
The role of information in fishery development becomes very important now. The information represents source forunderstanding creation, opening of knowledge and assisting in efficient and effective decision-making. Growth ofscience and technology especially in submitting information by using media oblige fishermen for more selectivechosen source of effective information so they will be able to facilitate effort system of fishery catch. The purpose ofthis research was to know the characteristic of fishermen in Parangtritis village, to know access information sourceand to study the characteristic relation of fishermen access to the information source. This research was executed atParangtritis village, Sub district of Kretek, Bantul Regency, Yogyakarta in March - May 2004 by using correlationdescriptive method. Data collecting was conducted by using structured interview with questioner. Result of researchindicates that the fishermen generally are in productive age, most of fishermen status is a laborer, formal educationof fishermen generally is junior high school and senior high school, and they have followed non formal education.Their earnings are between Rp.500.000 - Rp. 1.000.000. The fishermen generally access the interpersonal mediainformation source by way of humanity communication and group, newspaper and electronic media - radio andTelevision. Result of research indicates that only some components of characteristic relate to access of informationsource by interpersonal media, press and the electronic. Fishermen status have a negative real correlation withinformation access through radio, non formal education of fisheries has a very real correlation with informationaccess through communications among fishermen and television media, has a real correlation with informationaccess in groups and newspaper media. While fishermen earnings have a real negative correlation with informationaccess by Sub district Worker of Fishery (PPK), very negative correlation with information access by “layar tancap”film and VCD media.